Government at a Glance 2015. - (:unkn) unknown (My University, 2015)
Government at a Glance provides readers with a dashboard of key indicators assembled with the goal of contributing to the analysis and international comparison of public sector performance. Indicators on government revenues, expenditures, and employment are provided alongside key output and outcome data in the sectors of education, health and justice. It also includes indicators on key governance and public management issues, such as transparency in governance, regulatory governance, public procurement and the implementation of employment and remuneration reforms since 2009. While measuring government performance has long been recognized as playing an important role in increasing the effectiveness and efficiency of the public administration, following the economic crisis and fiscal tightening in many member countries, good indicators are needed more than ever to help governments make informed decisions regarding tough choices and help restore confidence in government institutions. provides readers with a dashboard of key indicators assembled with the goal of contributing to the analysis and international comparison of public sector performance. Indicators on government revenues, expenditures, and employment are provided alongside key output and outcome data in the sectors of education, health and justice. Government at a Glance also includes indicators on key governance and public management issues, such as transparency in governance, regulatory governance, public procurement and the implementation of employment and remuneration reforms since 2009.
Keywords: Haushaltswesen; Finanzpolitik; Staat; Verschuldung; Verwaltung; Verwaltungsreform; Öffentlicher Sektor; Öffentliche Finanzen; Reformfähigkeit; Transparenz; Effizienz; Governance; Internationaler Vergleich; Glossar